Lamb wave propagation in vibrating structures for effective health monitoring - Lu, Xubin (2018)
Lamb wave based Structural Health Monitoring (SHM) has received much attention during the past decades for its broad coverage and high sensitivity to damage. Lamb waves can be used to locate and quantify damage in static structures successfully. Nonetheless, structures are usually subjected to various external vibrations or oscillations. Not many studies are reported in the literature concerning the damage detecting ability of Lamb wave in oscillating structures which turns out to be a pivotal issue in the practical application of the SHM technique. For this reason in this study, the propagating capability of Lamb waves in a vibrating thin aluminum plate is examined experimentally. Two circular shaped piezoelectric wafer active transducers are surface-bonded on the aluminum plate where one acted as an actuator and another as a sensor. An arbitrary waveform generator is connected to the actuator for the generation of a windowed tone burst on the aluminum plate. An oscilloscope is connected to the sensor for receiving the traveled waves. An external shaker is used to generate out-of-plane external vibration on the plate structure. Time of flight (TOF) is a crucial parameter in most Lamb wave based SHM studies, which measures wave traveling time from the actuator to sensor. In the present study the influence of the external vibrations on the TOF is investigated. Experiments are performed under different boundary conditions of the plate, such as free-free and fixed by gluing. The effects of external vibrations in the frequency range between 10 Hz to 1000 Hz are analyzed. Comparisons are carried out between the resulting Lamb wave signals from the vibrating plate for different boundary conditions. Experimental results show that the external vibrations in relatively low frequency range do not change the TOF during the application of Lamb wave based SHM.